The Effects of Shot Changes on Eye Movements in Subtitling - Izabela Krejtz; Agnieszka Szarkowska; Krzysztof Krejtz (Bern Open Publishing, 2013)
In this paper we address the question whether shot changes trigger the re-reading of subtitles. Although it has been accepted in the professional literature on subtitling that subtitles should not be displayed over shot changes as they induce subtitle re-reading, support for this claim in eye movement studies is difficult to find. In this study we examined eye movement patterns of 71 participants watching news and documentary clips. We analysed subject hit count, number of fixations, first fixation duration, fixation time percent and transition matrix before, during and after shot changes in subtitles displayed over a shot change. Results of our study show that most viewers do not re-read subtitlescrossing shot changes.